Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/ar3426
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in serum levels of S100A8/9 (calprotectin) correlate with improvements in total swollen joint count in patients with recent-onset rheumatoid arthritis

Abstract: IntroductionThe aim of this study was to examine the serum levels of S100 proteins and to evaluate their role in patients with recent-onset rheumatoid arthritis (RA).MethodsSerum levels of S100A8/9 and S100A12 were analysed in 43 patients with recent-onset RA, both before and three months after the initiation of conventional treatment, as well as in 32 healthy individuals. Disease activity was assessed based on serum levels of C-reactive protein (CRP), the Disease Activity Score for 28 joints (DAS28) and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 24 publications
1
37
1
2
Order By: Relevance
“…Based on studies on the serum levels of S100A8, which in healthy controls range from 1058 to 6175 ng/mL, 44,45 we used rhS100A8 at four concentrations (0.1, 1, 2, and 4 mg/mL) compared with untreated controls to simulate the extracellular actions of S100A8 on tumor cells. Our in vitro results revealed that the transcriptional levels of SNAIL and BCL2 were significantly downregulated after high concentrations (2 or 4 mg/mL) of rhS100A8.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies on the serum levels of S100A8, which in healthy controls range from 1058 to 6175 ng/mL, 44,45 we used rhS100A8 at four concentrations (0.1, 1, 2, and 4 mg/mL) compared with untreated controls to simulate the extracellular actions of S100A8 on tumor cells. Our in vitro results revealed that the transcriptional levels of SNAIL and BCL2 were significantly downregulated after high concentrations (2 or 4 mg/mL) of rhS100A8.…”
Section: Discussionmentioning
confidence: 99%
“…These cell populations are all elevated in the peripheral blood of patients with ulcerative colitis (UC), secrete pro-inflammatory cytokines, and correlate with levels of intestinal inflammation [22,23]. Serum levels of calprotectin are elevated in some inflammatory conditions, and selective removal of peripheral blood activated granulocytes and monocytes/macrophages leads to a decline in fecal calprotectin levels in patients with UC [24,25]. Some studies have demonstrated that calprotectin in the stool can be a good marker to evaluate the activity of the disease as well as predict its severity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin has been shown to be sensitive to change as well as a strong predictor of response to biologic DMARDs (bDMARDs) in patients with established RA who did not respond satisfactorily to csDMARDs,23–25 although data are somewhat conflicting 10. In early RA, calprotectin has been shown to decrease with csDMARD therapy,8 and one study showed high baseline levels to predict response to methotrexate in patients with active disease (ie, DAS28>3.2) 26. Baseline calprotectin is associated with levels as well as presence of anti-citrullinated peptide antibody (ACPA) and rheumatoid factor (RF) 10 27 28.…”
Section: Introductionmentioning
confidence: 99%